Perancangan Prototype Tirai Hujan Otomatis Berbasis Arduino - Nabil Radityo B.P; Kinanti Ayu Hasanah; Darryl Endra Zachary; Adli Ahmad Hazimulfikri; Akila Shina Kusumaningrum; Aliya Rusyda Muthmainah (LPPM POLITEKNIK LP3I BANDUNG, 2024)
Sensors are an important element in the automation process. The automation process itself is one of the important concepts in smart living, which allows us to live more comfortably with the help of certain technological devices, which generally use sensors. The combination of sensors with microcontrollers can help us do a job automatically. One of them is to close the curtains automatically in case of rain. This process can be done by connecting a sensor to detect rainwater or a raindrop sensor, with an Arduino microcontroller, and a motor to move the curtain. This research aims to design an automatic rain curtain prototype using a raindrop sensor as a rainwater detector. This prototype is built using MH-RD raindrop sensor, Arduino Uno R3 and 995 180o servo motor. This device is then simulated on a model in the form of a mini house mockup equipped with a rain protection curtain for clothespins and tested by spraying 5ml of water using a mini sprayer 3 times. The simulation results show that the curtain can close automatically when the sensor is splashed with water, and reopen when the sensor does not detect water.